Early Stroke Rehabilitation of the Upper Limb Assisted with an Electromyography-Driven Neuromuscular Electrical Stimulation-Robotic Arm - Qian, Qiuyang; Hu, Xiaoling; Lai, Qian; Ng, Stephanie C.; Zheng, Yongping; Poon, Waisang (Frontiers in Neurology, 2017)
Background: Effective post-stroke motor rehabilitation depends on repeated limb practice with voluntary efforts. An electromyography (EMG) driven neuromuscular electrical stimulation (NMES)-Robot arm was designed for the multi-joint physical training on the elbow, the wrist and the fingers. Objectives: To investigate the training effects of the device assisted approach on subacute stroke patients and to compare the effects with those achieved by the traditional physical treatments. Method: This study was a pilot randomized controlled trial with a 3-month follow-up. Subacute stroke participants were randomly assigned into two groups, and then received 20-session upper limb training with the EMG-driven NMES-robotic arm (NMES-robot group, n=14) or the time-matched traditional therapy (the control, n=10). For the evaluation of the training effects, clinical assessments including Fugl-Meyer Assessment (FMA), Modified Ashworth Score (MAS), Action Research Arm Test(ARAT) and Function Independence Measurement(FIM) were conducted before, after the rehabilitation training, and 3 months later. Session-by-session EMG parameters in the NMES-robot group, including normalized co-contraction Indexes (CI) and EMG activation level of target muscles, were used to monitor the progress in muscular coordination patterns. Results: Significant improvements were obtained in FMA(full score and shoulder/elbow), ARAT and FIM(P<0.001, effect sizes>0.279) for both groups. Significant improvement in FMA wrist/hand was only observed in the NMES-robot group (P<0.001, effect size=0.435) after the treatments. Significant reduction in MAS wrist was observed in the NMES-robot group after the training (P<0.05, effect sizes=0.145) and the effects were maintained for 3 months. MAS scores in the control group were elevated following training (P<0.05, effect sizes>0.24), and remained at an elevated level when assessed three months later. The EMG parameters indicated a release of muscle co-contraction in the muscle pairs of biceps brachii and flexor carpi radialis and biceps brachii and triceps brachii, as well as a reduction of muscle activation level in the wrist flexor in the NMES-robot group. Conclusions: The NMES-robot assisted training was effective for early stroke upper limb rehabilitation and promoted independence in the daily living comparable to the traditional physical therapy. It could achieve higher motor outcomes at the distal joints and more effective release in muscle tones than the traditional therapy.